Holocene Paleo‐Geographic Reconstructions of the Ramore Head Area, Northern Ireland, Using Geophysical and Geotechnical Data: Paleo‐Landscape Mapping and Archaeological Implications. Issue 6 (30th September 2014) - Westley, Kieran; Plets, Ruth; Quinn, Rory
<x xml:space="preserve">Abstract</x> We present early to Mid‐Holocene paleo‐geographic reconstructions for the Ramore Head area (Northern Ireland). This coastal area is characterized by Mesolithic occupation (c. 10–6 ka) and preserved early–Mid‐Holocene peats both on‐ and offshore. This paper improves on previous reconstructions by employing a backstripping methodology, which removes accumulated recent deposits from identified buried paleo‐landsurfaces instead of using modern topography as an analogue to the past landscape. Paleo‐landsurfaces are identified offshore from seismic profiles supplemented by cores, and onshore through legacy borehole records. The paleo‐landsurface can be traced offshore to depths of −2 to −19 m and is buried by <5 m of modern sediment. It extends onshore under the coastal town of Portrush and is buried <2.5–10 m below modern ground level. The identified paleo‐landsurface is combined with sea‐level curves from recent Glacio‐Isostatic‐Adjustment models to reconstruct marine transgression during the early–Mid‐Holocene. Comparison is also made with reconstructions based on modern topography. Together, the identified paleo‐landsurfaces and revised reconstructions can assist future site prospection on‐ and offshore and delimit high‐potential areas for heritage management. Revised reconstructions also allow placement of extant archaeology into a more accurate context of landscape change and help develop insights into local‐scale site location patterns.